A new xandarellid euarthropod from the Cambrian Chengjiang biota, Yunnan Province, China. (3rd December 2018) - Hou, Xianguang; Williams, Mark; Sansom, Robert; Siveter, Derek J.; Siveter, David J.; Gabbott, Sarah; Harvey, Thomas H. P.; Cong, Peiyun; Liu, Yu
Abstract: The euarthropod Luohuilinella deletres sp. nov. is described from rare material from the Chengjiang biota, Cambrian Series 2, Stage 3, of Yunnan Province, China. Phylogenetic analysis recovers a xandarellid affinity for L. deletres, representing only the fifth described species of this clade. L. deletres possesses a head shield that is about one-fifth of the total body length and a trunk with 30 tergites, the reduced anterior-most tergite and terminal three tergites lacking pleural elongations. Anteriorly situated notches in the head shield are associated with stalked eyes, in contrast to the more posterior, enclosed eye slits present in Xandarella . Posterior to the antennae there are at least 11 pairs of biramous appendages preserved, including three pairs in the head. The morphology of the midline gut of L. deletres, in which lateral, unbranched diverticula are wider towards the front of the body, is a characteristic also found in various trilobites. The dorsoventrally flattened exoskeleton suggests a benthic or nektobenthic mode of life for L. deletres, as for other trilobitomorphs, and it likely used its well-developed anteriorly positioned eyes for searching out food, either to scavenge or to find prey.